Pengaruh Foaming Agent Terhadap Porositas dan Densitas Cellular Lightweight Concrete - Fahreza, Rizky; Ary Wahyudie, Ilham; Sukanto, Sukanto (Jurnal Inovasi Teknologi Terapan, 2023)
With the rapid development of the industry at this time emerged a variety of technologies that developed, one of which was the food and beverage industry. The use of plastic in packaging is one of the reasons for the accumulation of waste. Handling that can be done is to process the plastic waste into one of the materials added to manufacture lightweight bricks. Lightweight brick is a material that has a lower mass than conventional brick. This study aimed to determine the effect of foaming agent variations on the density and porosity of lightweight bricks and to prove the hypothesis that variations in foaming agent affect density and porosity by analysis of variance. The test objects in this study were in the form of blocks of 100 mm × 50 mm × 50 mm in 27 variations and with three replications with 81 samples of the test objects. From this research, the best density value was 666.72 kg/m3 using an 85 cm3 foaming agent with porosity values ranging from 0.01 to 0.42%.